A importância dos estudos da Crítica Textual para a tradução literária: análise da tradução de dois poemas de Emily Dickinson - Souza, Mariana Ribeiro de (TradTerm, 2011)
This article deals with the analysis of the essay “Questions of diction and poetic creation in the translation of Emily Dickinson" by the translator, poet and writer José Lira in the light of the studies of textual criticism. It attempts to consider how the knowledge of the concepts of modern textual criticism can help the literary translator in his translation process. This discussion refers to the heart of the discussion in the study of textual criticism and translation studies in literature: the question of the interpretation of literary works. José Lira, in his essay on the translation of poems by Emily Dickinson, shows how he makes his “definitive” choices during the translation of her poems. It is in pursuit of this creative process of the poet that he finds his own. The translator uses the studies of modern textual criticism to find the voice of the writer and his own.